过渡经济银企关系问题研究 = A study on the bank-enterprise relationship in transitory economy - 李国勇 Li, Guoyong (2008)
This thesis starts with the definition of the relationship between banks and enterprises, a relationship which involves banks providing funding for corporation production and gaining interest and enterprises utilizing the money to obtain profits. To be more general, such relationship indicates the combination of financial capital and industrial capital.